Anomalous frequency trends in MoS2 thin ﬁlms attributed to surface effects - Luo, Xin (2014)
The layered dichalcogenide MoS2 has many unique physical properties in low dimensions. Recent experimental Raman spectroscopies report an anomalous blue shift of the in-plane E12g mode with decreasing thickness, a trend that is not understood. Here, we combine experimental Raman scattering and theoretical studies to clarify and explain this trend. Special attention is given to understanding the surface effect on Raman frequencies by using a force constants model based on first-principles calculations. Surface effects refer to the larger Mo-S force constants at the surface of thin film MoS2, which results from a loss of neighbours in adjacent MoS2 layers. Without surface effects, the frequencies of both out-of-plane A1g and in-plane E12g modes decrease with decreasing thickness. However, the E12g mode blue shifts while the A1g mode red shifts once the surface effect is included, in agreement with the experiment. Our results show that competition between the thickness effect and the surface effect determines the mechanical properties of two-dimensional MoS2, which we believe applies to other layered materials.